1996
DOI: 10.1007/bf00180810
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical antitumor activity of CI-994

Abstract: CI-994 [aka: acetyldinaline; PD 123654; 4-acetylamino-N-(2'aminophenyl)-benzamide] (Figure 1) is a novel antitumor agent with a unique mechanism of action. It is the acetylated metabolite of dinaline, a compound previously identified as having cytotoxic and cytostatic activity against several murine and human xenograft tumor models. CI-994 had activity against 8/8 solid tumors tested (log cell kills at the highest non-toxic dose): pancreatic ductal adenocarcinoma #02 (4.7); pancreatic adenocarcinoma #03 (3.0; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…1,2 Despite the demonstration of impressive activity in vivo, very little is known about its mechanism of action. A recent study by Gao et al 3 suggests that XK469 may act as a topoisomerase II␤ poison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Despite the demonstration of impressive activity in vivo, very little is known about its mechanism of action. A recent study by Gao et al 3 suggests that XK469 may act as a topoisomerase II␤ poison.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, XK469 was selected through a disk-diffusion soft agar colony-formation assay and was found to have selective antiproliferative activity for solid tumors. 1,2 Despite the demonstration of impressive activity in vivo, very little is known about its molecular targets and mechanism of action. A recent study by Gao et al 3 showed that XK469 might be a selective topoisomerase II␤ poison with functional activity similar to that of the topoisomerase II inhibitor 4Ј-(9-acridinylamino) methanesulfon-m-anisidide (m-AMSA).…”
mentioning
confidence: 99%
“…CI994, a small molecule (MW=269.3) and with poor aqueous solubility, was developed as an acetylated analogue of Dinaline (GOE-1734), which, also showed equivalent antitumor activity (LoRusso et al, 1996). CI994 was eventually identified as an active metabolite of Dinaline (LoRusso et al, 1996).…”
Section: Ci994 (N-acetyldinaline)mentioning
confidence: 99%
“…CI-994 (N-acetyl dinaline) is a novel substituted benzamide derivative with cytotoxic activity in preclinical models (LoRusso et al, 1996). Although the precise mechanism of action is not completely understood, CI-994 appears to work with increase in acetylation of histones.…”
Section: Other Targetsmentioning
confidence: 99%